Enhanced corrosion resistance and hardness of CoCrCuFeNi alloy under high-pressure solidification. (March 2023) - Wang, Xiaohong; Tao, Yanbo; Yang, Xing; Deng, Yulei; Zhu, Dongdong; Dong, Duo; Ma, Tengfei
Abstract: This study adopts a high-pressure method to prepare a CoCrCuFeNi high-entropy alloy (HEA). The effects of high pressure on the microstructure, phase composition, hardness, and corrosion resistance of the alloy are studied. The Vickers hardness of the CoCrCuFeNi HEA solidified under ambient pressure and 4 GPa is determined to be 203.4 HV and 822.4 HV, respectively. This presents an approximately three-fold increase in hardness. The nanohardness of the matrix is also increased three-fold, and the value of the intergranular phase is increased by 0.2 times, which is attributed to the precipitation of a finer nano Cu-rich phase and nano Fe–Cr phase under high pressure. A more complete, dense, and uniform CoCrCuFeNi HEA passive film is obtained under high pressure, and the passivation film resistance (Rpass ) is increased by 1.3 times. From a polarization curve test, the corrosion rates of the CoCrCuFeNi HEA solidified under ambient pressure and 4 GPa are 0.0209 mm/a and 0.0076 mm/a, respectively. Thus, the corrosion rate is reduced by 64%. Highlights: Vickers hardness of CoCrCuFeNi high entropy alloy increased from 203.4HV to 822.4HV after solidification under the pressure of 4 GPa, which increased by 3.04 times. More and finer FCC2 nano precipitates are uniformly dispersed in the matrix at 4 GPa. Nano (Fe, Cr)-rich FCC1 phases are precipitated in the Cu-rich FCC2 phase at the grain boundary after solidified at 4 GPa. The corrosion rate is reduced by 63.6% at high pressure.